Southern cross - Cornwell, Patricia Daniels (New York : G.P. Putnam's Sons, 1998)
Police chief Judy Hammer and her team encounter corruption, scandal, and robberies escalating to murder in their attempt to clean up the police force in Richmond, Virginia.
Keywords: Police chiefs -- Virginia -- Richmond -- Fiction; Police -- Virginia -- Richmond -- Fiction; Policewomen -- Virginia -- Richmond -- Fiction; Hammer, Judy (Fictitious character); Richmond (Va.) -- Fiction; Mystery fiction